SCIENTIFIC-METHODOLOGICAL APPROACHES TO DETECTION OF A SOCIAL AND ECONOMIC FORECASTING - Tuyana B. Tsydypova (Статистика и экономика)
The article is devoted to the scientific approaches to detection of the intension of “social and economic forecasting”. Its role in the management of economic systems is considered. Problems solved at the stage of forecasting are identified. A current mechanism of state socio-economic forecasting is described.